Nonlinear model simulation of ship motion - Dao, Nguyen Van (Vietnam Journal of Mechanics, 1992)
Nonlinear model simulation of coupling between heave-roll and pitch roll ship motions is considered by means of the asymptotic method of nonlinear mechanics. The purely vertical motion and vertical-angular motion and their stability are studied.